Model of the sewage sludge-straw composting process integrating different heat generation capacities of mesophilic and thermophilic microorganisms. (September 2015) - Białobrzewski, I.; Mikš-Krajnik, M.; Dach, J.; Markowski, M.; Czekała, W.; Głuchowska, K.
Highlights: Mathematical model of the sewage sludge composting process was proposed. The set of 11 first-order differential equations were integrated. Kinetics of microbial growth, heat and mass transfer were predicted. Model predicts the development of two microbial groups: mesophiles and thermophiles. Abstract: A mathematical model integrating 11 first-order differential equations describing the dynamics of the aerobic composting process of sewage sludge was proposed. The model incorporates two microbial groups (mesophiles and thermophiles) characterized by different capacities of heat generation. Microbial growth rates, heat and mass transfer and degradation kinetics of the sewage sludge containing straw were modeled over a period of 36 days. The coefficients of metabolic heat generation for mesophiles were 4.32 × 10 6 and 6.93 × 10 6 J/kg, for winter and summer seasons, respectively. However, for thermophiles, they were comparable for both seasons reaching 10.91 × 10 6 and 10.51 × 10 6 J/kg. In the model, significant parameters for microbial growth control were temperature and the content of easily hydrolysable substrate. The proposed model provided a satisfactory fit to experimental data captured for cuboid-shaped bioreactors with forced aeration. Model predictions of specific microbial populations and substrate decomposition were crucial for accurate description and understanding of sewage sludge composting.